2021
DOI: 10.1016/j.heliyon.2021.e06253
|View full text |Cite
|
Sign up to set email alerts
|

Identification and evaluation of antioxidant and reference genes for quantitative real-time PCR in blood of Caiman latirostris

Abstract: The quantitative real-time polymerase chain reaction (qPCR) has been one of the most promising approaches to perform rapid and accurate quantification of DNA in various biological systems. The aim of this study was to standardized the qPCR technique for the analysis of important genes involved in the main routes of antioxidant defense against reactive oxygen species (catalase: cat and superoxide dismutase: sod) and evaluate the stability of different reference genes in blood of Caiman latirostris hatchlings. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Each reference gene has highly conservative and stable expression characteristics. However, recent studies have found that these commonly used reference genes are unstable, and their expression levels usually vary greatly in different types of cells and tissues, stages of development, and experimental treatments (Berruien et al 2021; He et al 2021; Odetti et al 2021). For this reason, specific reference genes must be rescreened in specific species.…”
mentioning
confidence: 99%
“…Each reference gene has highly conservative and stable expression characteristics. However, recent studies have found that these commonly used reference genes are unstable, and their expression levels usually vary greatly in different types of cells and tissues, stages of development, and experimental treatments (Berruien et al 2021; He et al 2021; Odetti et al 2021). For this reason, specific reference genes must be rescreened in specific species.…”
mentioning
confidence: 99%